The Impact of Service Quality and Employee Performance on Community Satisfaction: A Case Study in Serang Village - Fathya Azzahra; Herdiyanti (Jurnal Manajemen dan Profesional, 2026)
In the context of village governance, human resource management plays a crucial role in ensuring that officials provide optimal public services to achieve organizational goals effectively so that this research analyzes the influence of service quality and employee performance on community satisfaction in Serang Village, Salawu District, Tasikmalaya Regency. By implementing a quantitative method, data were obtained from 103 respondents via a purposive sampling technique with structured questionnaires and processed using the SPSS program. The findings indicate that service quality and employee performance partially exert a positive and significant influence on community satisfaction.